Perceived Organizational Support and Employee Job Performance . - Panthukampone, Panu; Chienwattanasook, Krisada (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
Perceived organizational support of employees can influence employee behaviour in various ways. In case of the employees who perceived the organisational supports in the high level, they will behave themselves in a way that they are willing to work for the organization in order to achieve the organization goal, commitment and engagement. This behaviour can positively result in employee performance. In contrast, if the employees perceive the supports from the organization in the low level, mismatching the expectation, it can result in employee performance. Therefore, the perceived organizational support is crucial for developing human resources because employee is accounted as the heart in driving the organization and crating the competitive advantages. The organization, which can be successful or failure, depends on employees in the organization. As aforementioned, this article emphasizes on creating the understanding of executives towards the advantages of establishing perceived organizational supports which it can lead to employee commitment, employee citizenship and employee performance. Article history : Received 8 January 2019 Revised 6 February 2019 Accepted 11 February 2019 SIMILARITY INDEX = 0.00